LONG-TERM DETERMINANTS OF ECONOMIC DEVELOPMENT: THE IMPACT OF MIGRATION FLOWS ON THE ECONOMY OF UKRAINE - Світлана Ткаленко; Жанна Дерій; Людмила Кудирко; Роксоляна Любачівська; Юлія Грицку-Андрієш; Вікторія Косицька (Фінансово-кредитна діяльність: проблеми теорії та практики)
The article examines the present issues with Ukraine's long-term economic development in light of migratory movements following the end of the war. The authors point out that factors like economic expansion, which would provide jobs for them and draw in foreign capital, digitization of the economy, increased use of ICT and digital technologies, and improvements in population welfare could be the main causes of the return of refugees following the conclusion of the war. The authors came to the conclusion that while the mass return of refugees may, in the short term, result in overcrowding and a rise in the unemployment rate, which will have a negative impact on GDP, it may also, in the long run, lead to the emergence of new industries or the revitalization of declining regions, both of which will have a positive impact on GDP growth. Programs for the repatriation of refugees should be established by the state to support such a positive trend. Reconstruction after a war can involve refugees, who will boost the economy. In light of this, public-private partnerships are crucial for Ukraine as they foster effective communication among its constituents and guarantee the promptness and dependability of efforts to rebuild the nation's economy, particularly in times of crisis and during the post-war era. A significant quantity of debt, which is created during times of war, bolsters the downward trend. It can also result in a decline in GDP because of the destruction of some industries, limited production capacity, and a reduction in economic efficiency.